Utfodring av föl före och efter avvänjning - Nilsson, Carolin (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
Swedish horse breeders have generally very few mares producing a few foals a year and the breeders have relatively few traditions, little knowledge and experience to breed foals successfully. It is therefore important to provide adequate information about new findings in horse nutrition. However, there is not much research about feeding the suckling foal to ensure a sound growth. Current feeding recommendations in the literature seems to be different. This gives a confusing message and the information is difficult to apply. This paper reviews some publications in the area of feeding the suckling and weaning foal. Most authors stress that it's important to start feeding the foal early in life. When the foal is three months old, the mare will start to have difficulties to fully supply nutrients to the foal. It is also natural for the foal to seek more additional feed sources at this age. Depending on the availability of grass, additional feeding may be necessary. The best way to do this is to feed the foal with a balanced concentrate and secure the availability of grass or high quality hay. The feeding of the concentrate is readily done by the use of creep feeding technology. The foal can here feed ad libitum without competition from mares. This allows them to feed in small portions, which is advantageous for the digestion. Foals should eat about 2 kilo concentrates at the time of weaning in order to avoid a growth depression because of low nutrient intake. A survey was also made among horse breeders and how they feed and wean their foals. The breeders were situated in Southern and Northern Sweden. Most breeders had the same type of feed management, but only few breeders fully used creep feeding technology at early age of the foals. Feeding of foals was mainly done a short time before weaning. Conclusively, it seems that breeders are not very aware of the benefits of when and how to creep feed foals and thus misses the opportunity to avoid problems like growth depressions at weaning and to have an optimal growth of the foal.